Optimization of Disk-Type External Rotor SRGs for Wind Power Generation - Lalarukh Haseeb; Yue Ping Mo; Muhammad Mudasser (International Journal of Electrical, Energy and Power System Engineering)
In small-scale wind power generation, the disk-type external rotor switched reluctance generator (SRG) emerges as a promising innovation, offering distinct advantages. This comprehensive study, through rigorous steady-state and dynamic simulations, meticulously examines the performance of a carefully designed disk-type external rotor SRG using advanced finite element analysis tools such as Maxwell and Simplorer. The simulation results validate the excellence of this novel design, demonstrating its capability to achieve commendable power generation in both steady-state and dynamic scenarios. The simulations provide strong evidence of the generator’s ability to maintain stability under varying operational conditions while consistently delivering promising power generation. This research contributes to the validation and recognition of the disk-type external rotor SRG as a reliable and efficient solution in direct-drive wind power systems. By highlighting the generator's robustness and efficiency, this study paves the way for the adoption of this innovative SRG design in practical applications, advancing wind power generation technology.